Survival Analysis after Living Donor Liver Transplantation for Hepatocellular Carcinoma: A Single Center Cohort Study - Byung-Gon Na; Seong-Hoon Kim; Sang-Jae Park (Biology, 2021)
Background: Living-donor liver transplantation (LDLT) for hepatocellular carcinoma (HCC) has been used as a curative treatment option for hepatocellular carcinoma (HCC) because of a shortage of deceased donors. This study aimed to investigate survival outcomes after LDLT for HCC. Method: This study included 359 patients undergoing LDLT for HCC. We analyzed overall survival (OS) and recurrence-free survival (RFS) and the prognostic factors related to them. Results: The 5-year OS and RFS rates of patients within the Milan criteria (WM) were better than those of patients beyond the Milan criteria (BM) (87.3% vs. 64.1% and 87.6% vs. 57.8%, respectively, both p < 0.05). Alpha-fetoprotein level (AFP) > 400 ng/mL (hazard ratio (HR), 2.07; 95% CI, 1.28–3.36; p < 0.05) and HCC of BM (HR, 2.61; 95% CI, 1.60–4.26; p < 0.05) at immediate pretransplant were independent risk factors of OS. AFP > 400 ng/mL (HR, 2.16; 95% CI, 1.34–3.49; p < 0.05) and HCC of BM (HR, 3.01; 95% CI, 1.81–5.01; p < 0.05) were also independent risk factors of RFS. In pathologic findings of explanted liver, tumor size, Edmondson–Steiner grade III–IV, and microvascular invasion were independent risk factors of both OS and RFS (p < 0.05). Conclusions: BM and AFP > 400 ng/mL at immediate pretransplant are unfavorable predictors of survival outcomes after LDLT for HCC.